The F1Fo-ATPase inhibitor protein IF1 in pathophysiology - Gatto, Cristina; Grandi, Martina; Solaini, Giancarlo; Baracca, Alessandra; Giorgio, Valentina (Frontiers in Physiology, 2022)
The endogenous inhibitor of ATP synthase is a protein of about 10 kDa, known as IF1 which binds to the catalytic domain of the enzyme during ATP hydrolysis. The main role of IF1 consists of limiting ATP dissipation under condition of severe oxygen deprivation or in the presence of dysfunctions of mitochondrial respiratory complexes, causing a collapse in mitochondrial membrane potential and therefore ATP hydrolysis. New roles of IF1 are emerging in the fields of cancer and neurodegeneration. Its high expression levels in tumour tissues have been associated with different roles favouring tumour formation, progression and evasion. Since discordant mechanisms of action have been proposed for IF1 in tumors, it is of the utmost importance to clarify them in the prospective of defining novel approaches for cancer therapy. Other IF1 functions, including its involvement in mitophagy, may be protective for neurodegenerative and aging-related diseases. In the present review we aim to clarify and discuss the emerging mechanisms in which IF1 is involved, providing a critical view of the discordant findings in the literature.